Análise comparativa de ligação com pinos metálicos, pregos e parafusos em estrutura de madeira - Kozerski, Carlos Eduardo (2012)
The wooden structures require parts with dimensionsand geometric shapes that are hardly found convenient to use structural or expected. To viability of these structures, it is necessary to make connections and / or amendments to ensure strength, durability and safety. Making the connection between elements is one of the most important aspects for designers andbuilders. Thus, this study aims to examine experimentally central three configurations connecting metal pins, one screwed, nailed another and also the combination ofnails and screws. The samples were subjected to compressive stress in the direction parallel to the wood fibers, this being a type commonly used in connection flanges of hedge shears. The classification rule comes as metal pins screws and nails, using the same calculation methodology for sizing. However, the screws have demonstrated superior strength, and observations mixed in binding were observed in larger deformations around the screw, indicating that higher loading absorbed, demonstrating the importance of conducting experimental tests for connections wooden structures.